2015
DOI: 10.1002/ps.3983
|View full text |Cite
|
Sign up to set email alerts
|

Neonicotinoid‐induced resurgence of rice leaffolder, Cnaphalocrocis medinalis (Guénee)

Abstract: Stimulated fecundity on neonicotinoid-sprayed plants, coupled with reduced larval duration and low egg toxicity, could be the major factors contributing to the upsurge of leaffolder. This study aids in cautioning farmers to be more vigilant while using imidacloprid and thiamethoxam, particularly in rice fields where leaffolder exists alongside planthoppers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…; Chintalapati et al. ). Insecticides may also increase pest densities by eliminating natural enemies (Kenmore et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Chintalapati et al. ). Insecticides may also increase pest densities by eliminating natural enemies (Kenmore et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported similar increases in pest damage after insecticide applications to rice. This can be the result of physiological responses to pesticides that induce greater feeding and increased reproductive output (Singh et al 1995;Azzam et al 2009;Suri and Singh 2011;Horgan et al 2014;Chintalapati et al 2016). Insecticides may also increase pest densities by eliminating natural enemies (Kenmore et al 1984;Cohen et al 1994).…”
Section: The Effects Of Insecticide Treatmentsmentioning
confidence: 99%
“…For example, where leaffolder (Cnaphalocrocis medinalis) incidence occurs along with planthoppers (Nilaparvata lugens) in rice fields of India, the use of neonicotinoids has resulted in increases of the leaffolder population. Stimulated fecundity of the leaffolder bugs on neonicotinoid-sprayed plants, coupled with reduced larval duration and low egg toxicity, were the major factors contributing to the upsurge of leaffolders (Chintalapati et al 2016).…”
Section: Impacts On Natural Systems For Pest and Weed Controlmentioning
confidence: 99%
“…Several recent surveys of rice farmers in Asia also indicate a high level of pesticide use and little recourse to alternative pest control methods (Rejesus et al, 2012;Qiao et al, 2012;Abdollahzadeh et al, 2015). Paradoxically, the trend towards an increasing availability of chemical pesticides has not resulted in the expected lower pest and weed incidences, but to area-wide problems of resistant weeds (Powles and Shaner, 2001), sustained outbreaks of planthoppers and leaf folders (Crambidae) (Sprangenberg et al, 2015;Chintalapati et al, 2016), unstable management of snails (Horgan et al, 2014b) and worrisome consequences for environmental and human health (Pingali and Roger, 1995;Qiao et al, 2012), often without clear yield responses to chemical inputs (Pingali and Gerpacio, 1997;Sprangenberg et al, 2015).…”
Section: Increased Availability and Marketing Of Agrochemicalsmentioning
confidence: 99%
“…In addition, several insecticides are associated with faster growth rates and increased reproduction in pest insects (Fig. 4) (Wang et al, 2005;Azzam et al, 2009;Chintalapati et al, 2016). To further add to the problem, the efficiency of natural enemies such as spiders and predatory wasps is reduced by insecticides either because they are directly killed by the chemicals or because their behaviours are altered (Kenmore et al, 1984;Tanaka et al, 2000;Horgan et al, 2017a).…”
Section: Insecticidesmentioning
confidence: 99%